1981
DOI: 10.21273/hortsci.16.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Thinning ‘Loring’ Peaches with CGA 15281

Abstract: Adequate fruit thinning of ‘Loring’ peach [Prunus persia (L.) Batsch] was achieved with single applications of (2-chloroethyl)-methylbis (phenylmethoxy) silane (CGA 15281) at concentrations of 240, 360, and 480 ppm applied at seed length of 8.8 mm and 2 applications at 240 and 360 ppm applied 7 days apart at 8.8 and 10.8 mm seed lengths in 1978. Additional hand thinning following treatment was required. In 1979 adequate thinning was achieved with 1 application of 240 ppm applied at seed length of 13.9 mm or 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
1

Year Published

1982
1982
1995
1995

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
(13 reference statements)
0
2
1
Order By: Relevance
“…Leaf abscission with CGA 15281 tends to be slight in most cases (3). Some leaf abscis sion was noted in the present study when higher concentrations were applied to the foliage but leaf abscission was not severe at any concentration in these tests.…”
contrasting
confidence: 44%
See 1 more Smart Citation
“…Leaf abscission with CGA 15281 tends to be slight in most cases (3). Some leaf abscis sion was noted in the present study when higher concentrations were applied to the foliage but leaf abscission was not severe at any concentration in these tests.…”
contrasting
confidence: 44%
“…Successful peach chemical thinning with ethylene-generating chemicals at ovule length of 7 to 12 mm is well documented (2, 4 ,7 ). Data have shown that the sensitivity of peaches to thinning increases as the peach develops during stage I (the initial period of rapid fruit growth) to early stage II (pit har dening) (3,4,7).…”
mentioning
confidence: 99%
“…Thus, the differences in stem tissue respiration de tected in this study may be related to differ ences in carbohydrate metabolism, which may directly or indirectly influence suscepti bility to cold injury. 4,5). Although (2-chloroethyl)phosphonic acid (ethephon), an ethylene-generating ma terial, has considerable blossom-thinning ef fect (2,7,8), the successful use of CGA as a blossom thinner has not been reported.…”
mentioning
confidence: 99%